EFFECT OF PH AND ADSORBENT DOSES ON MN (II) METAL ADSORPTION IN THE KALIGARANG RIVER SEMARANG CITY USING SYNTHETIC COCONUT SHELL POWDERED ACTIVATED CARBON (PAC) - Pradnya, Irene Nindita; Triwibowo, Bayu; Wulansarie, Ria; Hanifah, Ririn; Prakasita, Iffat Ganjar Fadhila (CENDEKIA EKSAKTA, 2023)
Kaligarang River is the largest river in the Semarang, which looks clear but actually containing Mn metal above the permitted threshold. Excessive presence of Mn metal can cause problems for human being, which can agglomerate inside the brain, liver, and kidneys.Moreover, it can lead to Parkinson's syndrome and damaging the central nervous system. The river water sample testing conducted at Tirta Moedal PDAM, Semarang; contaminated with heavy metal Mn of 1.075 mg/L. Based on Government Regulation No. 82 of 2001, the maximum allowable concentration of Mn in water is 0.1 mg/L. Adsorption with activated carbon is an effective and efficient method in processing Mn metal pollution. Activated carbon formed as powderis from coconut shell synthetic, with trademark Haycarb particle size of 500 microns. The adsorption process was carried out with a contact time of 90 minutes with a stirring speed of 210 rpm. The pH variables were pH 3, 7, and 12 and the adsorbent dose was 1, 5, 10 and 15 g /L. The adsorption results showed that the optimum conditions of the adsorption process occurred at pH 3 with an adsorbent dose of 15 g / L with percent absorption of manganese metal (Mn) of 87.18%.